2018
DOI: 10.36290/vnl.2018.131
|View full text |Cite
|
Sign up to set email alerts
|

CD38 targeted treatment for multiple myeloma

Abstract: SouhrnAntigen CD38 je uniformně a vysoce exprimován na plazmatických buňkách a stal se tak ideálním cílem pro léčbu mnohočetného myelomu (MM) pomocí anti-CD38 cílených monoklonálních protilátek (mAbs). Nejdále ve vývoji je daratumumab, nicméně podobně slibných výsledků dosahuje i isatuximab, který cílí na zcela jiný epitop molekuly CD38. Anti-CD38 mAbs mají pleiotropní mechanizmus účinku, který je popisován i u jiných mAbs, nicméně zásadním, novým a specifickým mechanizmem je tzv. imunomodulační efekt díky dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Accordingly, most preclinical and clinical MM studies to date have focused on the key immunotherapy antigens BCMA, CD38 and SLAMF7, with the latter two being the target of three already FDA-approved mAbs. BCMA, CD38 and SLAMF7 represent three key antigens in the biology of MM; the first plays a key role in B cell maturation and differentiation into PCs and is upregulated in disease progression from MGUS to SMM and active MM ( 15 ); the second is uniformly expressed on PCs and is involved in modulating immune cell activation and migration ( 9 ), while the latter is involved in the development of immune system and promotes PCs proliferation and growth ( 13 ). Given its central role in MM biology, restricted expression on normal PCs but strong upregulation on malignant cells, BCMA has become the most common target of various therapeutic strategies, each associated with logistical challenges and unique toxicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, most preclinical and clinical MM studies to date have focused on the key immunotherapy antigens BCMA, CD38 and SLAMF7, with the latter two being the target of three already FDA-approved mAbs. BCMA, CD38 and SLAMF7 represent three key antigens in the biology of MM; the first plays a key role in B cell maturation and differentiation into PCs and is upregulated in disease progression from MGUS to SMM and active MM ( 15 ); the second is uniformly expressed on PCs and is involved in modulating immune cell activation and migration ( 9 ), while the latter is involved in the development of immune system and promotes PCs proliferation and growth ( 13 ). Given its central role in MM biology, restricted expression on normal PCs but strong upregulation on malignant cells, BCMA has become the most common target of various therapeutic strategies, each associated with logistical challenges and unique toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a safer and durable response in MM patients several studies have identified key antigens overexpressed on malignant PCs essential for MM progression, and innovative targeted therapeutic strategies have been developed against them, mainly based on monoclonal antibodies (mAbs), immunoconjugates, synthetic peptides, and adaptive cellular therapies (see below). In addition to the widely studied MM-related antigens CD38 ( 9 11 ) and signaling lymphocyte activation molecule F7 (SLAMF7) ( 12 14 ), against which three mAbs have already received FDA approval for clinical use ( 10 , 14 ), and the B-cell maturation antigen (BCMA) ( 15 , 16 ), there is growing evidence for the key role of Syndecan1 (CD138 or SDC1), a transmembrane heparan sulfate proteoglycan (HPSG), in MM tumorigenesis ( 17 19 ). CD138 is highly expressed on malignant PCs and is involved in several cellular pathways responsible for their growth, survival, and proliferation by binding many growth factors and proteins in the extracellular matrix (ECM) ( 17 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CD38 antigen represents a frequently expressed antigen on plasma cells which makes them an excellent target for treatment in multiple myeloma (MM) by anti-CD38 directed agents [76]. Daratumumab, an anti-CD38 antibody, has demonstrated efficacy in MM by inducing Fc-mediated cell lysis by cell-mediated toxicity and complement activation [77].…”
Section: Cd38-directed Agents and Risk Of Infectionmentioning
confidence: 99%
“…The CD38 antigen represents a frequently expressed antigen on plasma cells, which makes them an excellent target for treatment in multiple myeloma (MM) by anti-CD38-directed agents [ 72 ]. Daratumumab, an anti-CD38 antibody, has demonstrated efficacy in MM by inducing Fc-mediated cell lysis by cell-mediated toxicity and complement activation [ 73 ].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%